Immunization induces inflammation in the mouse heart during spaceflight - Alicia L. Veliz; Lorelei Hughes; Delia Carrillo; Michael J. Pecaut; Mary Kearns-Jonker (BMC Genomics)
Abstract Space travel is a growing area of interest and includes initiatives such as NASA’s Moon-to-Mars Mission. Reports on the cardiovascular effects of space travel reveal changes in morphology, metabolism, and function of the cardiovascular system. In this study, the cardiovascular response to immunization in space was studied in mice which were housed and immunized while on the International Space Station (ISS). Mice were immunized with tetanus toxoid combined with the adjuvant CpG (TT + CpG) and the effects of vaccination in space were studied using transcriptomics. Analysis of the mouse heart transcriptome was performed on flight control and flight-immunized mice. The results show that immunization aboard the ISS stimulates heightened inflammation in the heart via induction of the nuclear factor kappa B (NF-κB) signaling pathway to promote the release of the pro-inflammatory cytokines IFNγ, IL-17 and IL-6. Additional transcriptomic changes included alterations in the cytoskeleton and in the expression of transcripts associated with protection from oxidative stress. In summary, inflammation in the heart can occur following immunization in space. This investigation explores the impact of immune challenges on the heart and lays the groundwork for future research into additional cardiac alterations which can occur during spaceflight.